2021
DOI: 10.1080/14786419.2021.1983570
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity-guided isolation of compounds from Sophora flavescens with antibacterial activity against Acinetobacter baumannii

Abstract: Bioactivity-guided fraction of an extract of Sophora flavescens to identify antibacterial compounds against Acinetobacter baumannii, led to the isolation of two new compounds, (2″R)-5-methoxy-7-hydroxy-8-lavandulylchromone ( 13) and (2S,βS)-(-)-sophobiflavonoid CE (19), and 18 known flavonoids, (6aR,11aR)-(-)-maackiain (1), (2S)-(-)-8-prenylnaringenin (2), (2S)-(-)-exiguaflavanone K (3), (2S)-(-)-sophoraflavanone G (4), (2S)-(-)-leachianone A (5), (2S)-(-)-kushenol E (6), (2S)-(-)-leachianone G (7), (±)-kushen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…MK is isolated from the traditional Chinese herbal medicine Kushen (dried roots of Sophora flavescens Aiton) [ 80 ]. MK has been reported to have multiple pharmacologic properties, such as anti-allergic [ 81 , 82 ], anti-inflammatory [ 44 , 83 ], anti-oxidative [ 44 ], anti-obesity [ 84 ], and antibacterial [ 85 ] activity in addition to neuroprotection [ 86 , 87 ]. In cancer therapy, MK can hinder the proliferation, migration, invasion, and foci formation of triple-negative breast cancer cells and thus has a significant inhibitory effect on tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…MK is isolated from the traditional Chinese herbal medicine Kushen (dried roots of Sophora flavescens Aiton) [ 80 ]. MK has been reported to have multiple pharmacologic properties, such as anti-allergic [ 81 , 82 ], anti-inflammatory [ 44 , 83 ], anti-oxidative [ 44 ], anti-obesity [ 84 ], and antibacterial [ 85 ] activity in addition to neuroprotection [ 86 , 87 ]. In cancer therapy, MK can hinder the proliferation, migration, invasion, and foci formation of triple-negative breast cancer cells and thus has a significant inhibitory effect on tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…The root of Sophora flavescens , also known as Kushen (Radix Sophorae Flavescentis), is commonly used to treat skin diseases and bacterial diarrhea in China and other Asian countries [21] , [22] . Previous studies have found that S. flavescens contains abundant alkaloids and flavonoids, which showed excellent antibacterial activity [23] , [24] . Sophoraflavanone G (SFG) and kurarinone (KE) are two representative lavandulylated flavonoids with the highest content in S. flavescens .…”
Section: Introductionmentioning
confidence: 98%
“…Sophoraflavanone G (SFG) and kurarinone (KE) are two representative lavandulylated flavonoids with the highest content in S. flavescens . Both showed potent antibacterial activity with a minimum inhibitory concentration (MIC) or fractional inhibitory concentration (FIC) <10 μg/mL and have a synergistic effect with common antibiotics [24] , [25] , [26] , [27] . They have been reported to inhibit bacterial growth by reducing the fluidity of cell membranes [28] .…”
Section: Introductionmentioning
confidence: 99%